The School of Salamanca a case of global knowledge production - Duve, Thomas, 1967-; Egío, José Luis; Birr, Christiane (Brill Nijhoff, 2021)
"This book proposes a different perspective and shows, through a knowledge historical approach and several case studies, that the School of Salamanca has to be considered both an epistemic community and a community of practice that cannot be fixed to any individual place. Instead, the School of Salamanca encompassed a variety of different sites and actors throughout the world and thus represents a case of global knowledge production"-- Provided by publisher.
Keywords: Alonso de la Vera Cruz, -- fray, -- approximately 1507-1584.; Alonso de la Vera Cruz, -- fray, -- approximately 1507-1584; Learning and scholarship -- History -- 16th century.; Learning and scholarship -- History -- 17th century.; Salamanca school (Catholic theology); Savoir et érudition -- Histoire -- 16e siècle.; Savoir et érudition -- Histoire -- 17e siècle.; Théologiens de Salamanque.; Learning and scholarship; 1500-1699; History